2020
DOI: 10.1038/s41419-020-2375-6
|View full text |Cite
|
Sign up to set email alerts
|

A Cdh1–FoxM1–Apc axis controls muscle development and regeneration

Abstract: Forkhead box M1 (FoxM1) transcriptional factor has a principal role in regulating cell proliferation, self-renewal, and tumorigenesis. However, whether FoxM1 regulates endogenous muscle development and regeneration remains unclear. Here we found that loss of FoxM1 in muscle satellite cells (SCs) resulted in muscle atrophy and defective muscle regeneration. FoxM1 functioned as a direct transcription activator of adenomatous polyposis coli (Apc), preventing hyperactivation of wnt/β-catenin signaling during muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…2e ). Moreover, beside its role in driving G2/M transition in embryonic (and cancer) stem cells 26 , 27 , FOXM1 controls self-renewal of both neural 28 and hematopoietic 29 stem cells, regeneration of striate muscles 30 and long-term maintenance of bronchiolar epithelium 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2e ). Moreover, beside its role in driving G2/M transition in embryonic (and cancer) stem cells 26 , 27 , FOXM1 controls self-renewal of both neural 28 and hematopoietic 29 stem cells, regeneration of striate muscles 30 and long-term maintenance of bronchiolar epithelium 31 .…”
Section: Resultsmentioning
confidence: 99%
“…But an important role of FOXM1 has been also reported in many stem cells 49 . In fact, FOXM1 (i) regulates the G2/M phase of the mammalian embryonic stem cell cycle and plays a role in protecting such cells from oxidative stress 26 ; (ii) controls a miRNA network involved in the self-renewal of murine neural stem cells 28 ; (iii) regulates Nurr1-mediated self-renewal of murine hematopoietic stem cells 29 ; (iv) controls satellite cell-mediated murine muscle regeneration through its interaction with the Wnt/β-catenin pathway 30 ; (v) is required for the proliferation and differentiation of murine Clara cells as well as for proper differentiation of airways epithelial, hence for long-term maintenance of the bronchiolar epithelium 31 ; (vi) is among the transcription factors marking highly proliferative murine clonogenic keratinocytes 50 . In cancer cells, FOXM1 regulates mostly cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These initial studies reported that FOXM1 is widely expressed in embryonic tissues but that its expression is restricted in adult tissues to actively proliferating cells, such as those in the thymus and gastrointestinal tract [ 12 , 13 , 14 , 18 ]. Indeed, later studies confirmed that FOXM1 is highly expressed in embryonic [ 19 , 20 , 21 , 22 ], regenerative [ 23 , 24 , 25 , 26 ], and cancerous tissues [ 27 , 28 , 29 ] and all of them exhibit high proliferative capacity. The FOXM1 field and publications have increased steadily since the year 2000, with a large proportion of studies focused on cancer ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of liver regeneration, hepatocyte-specific Foxm1 deletion slowed hepatocyte proliferation [ 78 ], while hepatocyte-specific FOXM1b overexpression led to accelerated hepatocyte growth through increased S-phase and M-phase transitions [ 46 , 79 , 80 ]. In mice challenged by lung injury, FOXM1b overexpression increased the proliferation of several cell types in the lung [ 81 ], while pancreas-wide Foxm1 deletion [ 82 ] and Foxm1 deletion in muscle satellite cells [ 26 ] led to impairments in pancreas and muscle repair, respectively, following injury. Collectively, studies using transgenic mice with Foxm1 KO, Foxm1 cKO, and FOXM1b overexpression verify an important role for FOXM1 in embryogenesis, organogenesis, and organ regeneration in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Upon injury, quiescent satellite cells in the myotome are activated and divide asymmetrically, resulting in renewal of the stem cell niche and the generation of new muscle fibers [27]. Mouse satellite cells express Foxm1, which contributes to proliferation and survival of these stem cells and proper muscle regeneration upon injury [33,34]. However, the high levels of Foxm1 expression in satellite cells decrease substantially, albeit not totally, upon differentiation into myofibers [33].…”
Section: Introductionmentioning
confidence: 99%